Analisa Volatile Matter dan Ash Content Briket Batubara Terhadap Penambahan Biomassa Sekam Padi - Lioe, Kon Phin; Wahyudie, Illham Ary; Yuliyanto, Yuliyanto (Manutech : Jurnal Teknologi Manufaktur, 2025)
One of the leading exports in Indonesia is coal and contributes significantly to the country's economy. However, there is coal that cannot be exported because it has a size dimension that is too small, therefore research is carried out to make briquettes. The purpose of this research is to get the best results from testing volatile matter and ash content with different temperatures, times, water:molasses fractions. The highest volatile matter test results were obtained from 100 ? temperature, 90 minutes time and water:molasses fraction (3:1) with a value of 31.73% and the lowest value was obtained from 120 ? temperature, 60 minutes time and water:molasses fraction (3:1) with a value of 23%. While the highest ash content test results were obtained from a drying temperature of 120 ?, time 90 minutes and water:molasses fraction (3:2) with a value of 48.6% and the lowest value was obtained from a drying temperature of 100 ?, time 60 minutes and water:molasses fraction (3:2) with a value of 41.83%. From the test results of volatile matter and ash content, it still does not meet SNI standards.